PERILAKU KEAGAMAAN DAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM DI SMA NEGERI 1 AMBARAWA KABUPATEN PRINGSEWU - Efendi, Rahmat (JURNAL MANAJEMEN PENDIDIKAN ISLAM AL-IDARAH, 2016)
Religious behavior student become a benchmark for the success of learning, especially learning Islam. Where the results of learning Islamic education not only from the aspect of cognitive but also affective and psychomotor aspects.Therefore, it is very interesting to do research if there is a relationship between religious behavior with Islamic education learning outcomes. The purpose of this study was to determine whether or not the relationship of religious behavior with Islamic education learning outcomes . The method used in this research is descriptive analysis method with quantitative research forms. The results showed no relationship between religious behavior with Islamic education learning outcomes. This conclusion is based on the correlation test was done using the formula Kendal tau test with SPSS. The test results show significant figures 0548> 0.05. Shown significant values greater than 0.05 means that there is a relationship between religious behavior of students with the learning outcomes of Islamic Education in SMA Negeri 1 Ambarawa Pringsewu.